PENGARUH PROMOSI DAN KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA RESTORAN BAKSO LAPANGAN TEMBAK SENAYAN - Diana Diana; Nanda Harry Mardika (Universitas Muhammadiyah Pringsewu, 2020)
The development of business today is characterized by increasingly intense competition,to be able compete with other culinary businesses, companies must pay attention to promotions, service quality and customer satisfaction. Attractive promotions and good service quality can increase customer satisfaction. The purpose of this study was to determine the existence of a positive and significant effect between promotion variables and service quality on consumer satisfaction at the Restoran Bakso Lapangan Tembak Senayan with a purposive sampling technique, the number of samples in this study amounted to 100 respondents. Data collection method is questionnaire. Data quality in this study uses validity and reliability test, the classic assumption and the influence test in this study using multiple linear regression analysis and coefficient of determination analysis (R2), while the hypothesis testing in this study uses t test and F test using SPSS version 23 software program. The results of the t test and F test, it can be concluded promotion is partially positive and significant effect on customer satisfaction, service quality is partially positive and significant effect on customer satisfaction, as well promotion and service quality as a whole. simultaneous positive and significant effect on consumer satisfaction in the Restoran Bakso Lapangan Tembak Senayan. Keywords: promotion, service quality, customer satisfaction